Kode, Bahasa, Dan Jenis Kalimat Bahasa Lisan Dosen PadaSituasi Resmi : Sebuah Kajian Sintaksis Serta ImplementasiSebagai Bahan Ajar Di SMP N 2 Kartasura - , Kiswadi, Drs. Agus Budi Wahyudi, M.Hum (2016)
The purpose of this research is. (1)Analysis the use of code language spoken lecturer in a formal situation. (2)Analysis the use of variety form of sentences spoken lecturer language in a formal situation. (3)Implementation of analyze the use of code language and variety of form of sentences spoken lecturer language in a formal situation as of teaching material in junior high school. This study using metod descriptive qualitative. The data source of this research obtained from 10 recording of spoken lecturer language in seminar on a theme education. Accumulaion data of this research using technique listening and note. Technique of validity data using trianggulasi theory. Technique analysis data use agih method. The object of this research is elements of language. As for the result of this research is (1)Founded data use of code language classified into three variety, namely using relaxed code, territory code, and foreign code. (2)Founded data divided into seven types of sentences, namely: declarative sentences, interogative sentences, imperative sentences, interjektif sentences, negative sentence, indirect sentences, and compound sentences. (3)Result of this research implemented as teaching material in SMPN 2 Kartasura class VII in second semester SK 9. Understand oral discourse through activities interview and KD 9.1 concluded, opinion, and the notion of speaker delivered in a interview. But, material learning is identify types of language code and sentences on spoken lecturer language in a formal situation. Keywords : Using code and type of sentence